Study on formation and properties of Al–Li–Sm alloy containing whiskers in molten salts. Issue 93 (11th October 2015) - Ji, De-Bin; Yan, Yong-De; Zhang, Mi-Lin; Li, Xing; Yang, Xue; Jing, Xiao-Yan; Han, Wei; Xue, Yun; Zhang, Zhi-Jian; Hartmann, Thomas
<x xml:space="preserve">Abstract</x> An Al–Li–Sm alloy containing whiskers was obtained by galvanostatic electrolysis in LiCl–KCl melts after the addition of 10 wt% SmCl3 on a liquid aluminum electrode at 973 K.